Acoustic measurements of supersonic jet flows - Wei, Xiaofeng (Nanyang Technological University, 2020)
There is an increasing interest in studying supersonic jet noise due to the immense noise level and poor understanding of the generation mechanisms. In many earlier studies, some nonuniform nozzle geometries were proposed to attain noise reductions in supersonic jets. However, the effectiveness and efficiency of noise reduction vary with the nozzle geometries and the fundamental mechanisms responsible for noise reduction are still unclear due to limitations of experimental measurement techniques for supersonic jet flows. Thus the present effort aims to study the noise radiated from different nonuniform nozzles to provide an experimental database for detailed characterizations. An equally important goal is to study acoustic properties in the near-field region to better understand the effect of nozzle exits on the generation of different noise components. In the present study, six lip-modified nozzles were designed and their detailed acoustic fields are compared to that of the circular baseline nozzle.